Special composite modified high-performance insulating injection molding material with flame retardant property for energy storage
By using soluble magnesium salts and aluminum salts to prepare composite epoxy modified flame retardant phenolic resins, combined with modified magnesium-aluminum composite flame retardant and grafted modified zeolites, the problems of poor flame retardant effect and environmental pollution in the prior art are solved, and the flame retardant effect and energy storage cycle of high-performance insulated injection molding are improved.
Patent Information
- Application Number
- CN202410918119.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-10
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the flame retardant phenolic resin molding material has a general flame retardant effect and causes serious damage to the environment during preparation, use and post-treatment.
Compound epoxy modified flame retardant phenolic resin is prepared using soluble magnesium salt and aluminum salt as raw materials, and additives such as modified magnesium-aluminum composite flame retardant and grafted modified zeolite are prepared to prepare composite modified high-performance insulated injection molding materials for energy storage with flame retardant properties.
It significantly improves the flame retardant effect and energy storage cycle, reduces environmental pollution, and enhances the toughness of the material.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of injection molding products, and in particular relates to a composite modified high-performance insulating injection molding material for energy storage with flame retardancy. Background Art
[0002] With the continuous development of the national economy, the modernization requirements for energy, electricity, transportation, communication, environmental protection and other fields are also constantly increasing. In the prior art, for example, the Chinese invention patent application publication number CN102875964A discloses a method for preparing a flame-retardant phenolic resin molding material, which uses decabromodiphenylethane as a flame retardant. On the one hand, its flame retardant effect is general during use, and on the other hand, it will cause serious damage to the environment during preparation, use and post-processing.
[0003] To this end, the present invention provides a composite modified high-performance insulating injection molding material specially used for energy storage with flame retardant properties. Summary of the invention
[0004] In view of the above problems existing in the prior art, the object of the present invention is to provide a composite modified high-performance insulating injection molding material for energy storage with flame retardant properties, which has the advantages of improved flame retardant effect and longer energy storage cycle.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] The flame retardant composite modified high-performance insulating injection molding material for energy storage is composed of the following parts by weight:
[0007] 20-35 parts of composite epoxy modified flame retardant phenolic resin; 14-30 parts of filler; 1-5 parts of polyethylene, 1-2 parts of dioctyl phthalate; 10-28 parts of additives; wherein the preparation process steps of the composite epoxy modified flame retardant phenolic resin are:
[0008] (1) mixing a soluble magnesium salt, a soluble aluminum salt and water to obtain a mixed solution, then dropping the mixed solution into an aqueous solution of sodium dodecylbenzene sulfonate, dropping an aqueous sodium hydride solution to maintain the pH value of the reaction system at 8 to 10, and filtering after the dropwise addition to obtain a modified magnesium-aluminum composite flame retardant;
[0009] The concentration of the sodium dodecylbenzene sulfonate aqueous solution is 0.01-0.04 mol / L, and the molar ratio of the soluble magnesium salt to the sodium dodecylbenzene sulfonate is 0.2-0.4:1;
[0010] (2) The modified magnesium-aluminum composite flame retardant is added in an amount of 1 to 5% of the weight of the phenolic resin, and the thermoplastic phenolic resin and the modified magnesium-aluminum composite flame retardant are blended and modified to obtain a composite epoxy modified flame retardant phenolic resin.
[0011] As a preferred technical solution of the present invention, the soluble magnesium salt is magnesium nitrate, and the soluble aluminum salt is aluminum nitrate.
[0012] As a preferred technical solution of the present invention, the filler is composed of light calcium carbonate and grafted modified zeolite in a weight ratio of 3:1-5.
[0013] As a preferred technical solution of the present invention, the grafted modified zeolite is prepared from the following raw materials in weight percentage: 8-16wt% of polyimide, 14-20wt% of polydimethylsiloxane, and the balance is zeolite; wherein the preparation method of the grafted modified zeolite is:
[0014] The zeolite is mechanically crushed to 0.5-1 mm, and then the crushed zeolite is washed with hydrochloric acid solution, alcohol and water for 4-6 times respectively and dried, and the treated zeolite is soaked in potassium nitrate solution for 40-60 minutes, the pretreated zeolite is mixed with water with a weight of 2.5-3 times of the pretreated zeolite, and then polydimethylsiloxane is added thereto and ball milled at a speed of 500-600 rpm for 10-15 minutes, and then polyimide is added thereto and ball milled at a speed of 2000-2500 rpm for 120-180 minutes, and finally dried to obtain the grafted modified zeolite.
[0015] As a preferred technical solution of the present invention, the zeolite is faujasite.
[0016] As a preferred technical solution of the present invention, the pH value of the reaction system is maintained at 8, 9 or 10.
[0017] As a preferred technical solution of the present invention, the concentration of the sodium dodecylbenzene sulfonate aqueous solution is 0.01 mol / L, and the molar ratio of the soluble magnesium salt to the sodium dodecylbenzene sulfonate is 0.2:1;
[0018] Or the concentration of the sodium dodecylbenzene sulfonate aqueous solution is 0.02 mol / L, and the molar ratio of the soluble magnesium salt to the sodium dodecylbenzene sulfonate is 0.3:1;
[0019] Or the concentration of the sodium dodecylbenzene sulfonate aqueous solution is 0.04 mol / L; the molar ratio of the soluble magnesium salt to the sodium dodecylbenzene sulfonate is 0.4:1.
[0020] As described above, the composite modified high-performance insulating injection molding material for energy storage with flame retardant properties according to the present invention has the following beneficial effects:
[0021] The present invention utilizes the above-mentioned flame-retardant energy storage special composite modified high-performance insulating injection molding material, and has the following advantages compared with the prior art:
[0022] (1) The present invention uses soluble magnesium salt and aluminum salt as raw materials to prepare composite epoxy modified flame retardant phenolic resin, and uses the modified flame retardant phenolic resin to prepare modified high-performance insulating injection molding material, which can further improve the flame retardant effect and longer energy storage cycle; and has less environmental pollution and is environmentally friendly.
[0023] (2) Experiments have found that adding dioctyl phthalate can enhance its toughness.
[0024] The present invention will be further described below in conjunction with specific implementation modes. DETAILED DESCRIPTION
[0025] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.
[0026] It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the limiting conditions that the present invention can be implemented, so they have no substantial technical significance. Any modification of the structure, change in the proportional relationship, or adjustment of the size should still fall within the scope of the technical content disclosed by the present invention without affecting the effects that the present invention can produce and the purposes that can be achieved. At the same time, the terms such as "upper", "lower", "left", "right", "middle" and "one" quoted in this specification are only for the convenience of description, and are not used to limit the scope of the implementation of the present invention. The change or adjustment of the relative relationship should also be regarded as the scope of the implementation of the present invention without substantial changes in the technical content. The specific structure can be described with reference to the drawings of the patent application.
[0027] Example 1
[0028] A composite modified high-performance insulating injection molding material for energy storage with flame retardant properties is composed of the following parts by weight: 20 parts of composite epoxy modified flame retardant phenolic resin; 14 parts of filler; 1 part of polyethylene, 1 part of dioctyl phthalate; 10 parts of additives; wherein the preparation process steps of the composite epoxy modified flame retardant phenolic resin are as follows:
[0029] (1) mixing a soluble magnesium salt, a soluble aluminum salt and water to obtain a mixed solution, then dropping the mixed solution into an aqueous solution of sodium dodecylbenzene sulfonate, dropping an aqueous sodium hydride solution to maintain the pH value of the reaction system at 8, and filtering after the dropwise addition to obtain a modified magnesium-aluminum composite flame retardant;
[0030] The concentration of the sodium dodecylbenzene sulfonate aqueous solution is 0.01 mol / L, and the molar ratio of the soluble magnesium salt to the sodium dodecylbenzene sulfonate is 0.2;
[0031] (2) The modified magnesium-aluminum composite flame retardant is added in an amount of 1% of the weight of the phenolic resin, and the thermoplastic phenolic resin and the modified magnesium-aluminum composite flame retardant are mixed and modified to obtain a composite epoxy modified flame retardant phenolic resin. The soluble magnesium salt is magnesium nitrate, and the soluble aluminum salt is aluminum nitrate. The filler is composed of light calcium carbonate and grafted modified zeolite in a weight ratio of 3:1 to 5.
[0032] Example 2
[0033] The composite modified high-performance insulating injection molding material for energy storage with flame retardant properties is composed of the following parts by weight: 26 parts of composite epoxy modified flame retardant phenolic resin; 20 parts of filler; 3 parts of polyethylene, 1.5 parts of dioctyl phthalate; 22 parts of additives; wherein the preparation process steps of the composite epoxy modified flame retardant phenolic resin are as follows:
[0034] (1) mixing a soluble magnesium salt, a soluble aluminum salt and water to obtain a mixed solution, then dropping the mixed solution into an aqueous solution of sodium dodecylbenzene sulfonate, dropping an aqueous sodium hydride solution to maintain the pH value of the reaction system at 9, and filtering after the dropwise addition to obtain a modified magnesium-aluminum composite flame retardant;
[0035] The concentration of the sodium dodecylbenzene sulfonate aqueous solution is 0.03 mol / L, and the molar ratio of the soluble magnesium salt to the sodium dodecylbenzene sulfonate is 0.3:1;
[0036] (2) The modified magnesium-aluminum composite flame retardant is added in an amount of 3% of the weight of the phenolic resin, and the thermoplastic phenolic resin and the modified magnesium-aluminum composite flame retardant are mixed and modified to obtain a composite epoxy modified flame retardant phenolic resin. The soluble magnesium salt is magnesium nitrate, and the soluble aluminum salt is aluminum nitrate. The filler is composed of light calcium carbonate and grafted modified zeolite in a weight ratio of 3:1 to 5.
[0037] Example 2
[0038] The composite modified high-performance insulating injection molding material for energy storage with flame retardant performance is composed of the following parts by weight: 35 parts of composite epoxy modified flame retardant phenolic resin; 30 parts of filler; 5 parts of polyethylene, 2 parts of dioctyl phthalate; 28 parts of additives; wherein the preparation process steps of the composite epoxy modified flame retardant phenolic resin are as follows:
[0039] (1) mixing a soluble magnesium salt, a soluble aluminum salt and water to obtain a mixed solution, then dropping the mixed solution into an aqueous solution of sodium dodecylbenzene sulfonate, dropping an aqueous sodium hydride solution to maintain the pH value of the reaction system at 10, and filtering after the dropwise addition to obtain a modified magnesium-aluminum composite flame retardant;
[0040] The concentration of the sodium dodecylbenzene sulfonate aqueous solution is 0.04 mol / L, and the molar ratio of the soluble magnesium salt to the sodium dodecylbenzene sulfonate is 0.4:1;
[0041] (2) The modified magnesium-aluminum composite flame retardant is added in an amount of 3% of the weight of the phenolic resin, and the thermoplastic phenolic resin and the modified magnesium-aluminum composite flame retardant are mixed and modified to obtain a composite epoxy modified flame retardant phenolic resin. The soluble magnesium salt is magnesium nitrate, and the soluble aluminum salt is aluminum nitrate. The filler is composed of light calcium carbonate and grafted modified zeolite in a weight ratio of 3:1 to 5.
[0042] In the above-mentioned embodiments 1, 2 and 3, the grafted modified zeolite is prepared from the following raw materials in weight percentage: 8-16wt% of polyimide, 14-20wt% of polydimethylsiloxane, and the balance is zeolite; wherein the preparation method of the grafted modified zeolite is:
[0043] The zeolite is mechanically crushed to 0.5-1 mm, and then the crushed zeolite is washed 4-6 times with hydrochloric acid solution, alcohol and water respectively and dried, and the treated zeolite is soaked in potassium nitrate solution for 40-60 minutes, and the pretreated zeolite is mixed with water 2.5-3 times the weight of the pretreated zeolite, and then polydimethylsiloxane is added thereto and ball milled at a speed of 500-600 rpm for 10-15 minutes, and then polyimide is added thereto and ball milled at a speed of 2000-2500 rpm for 120-180 minutes, and finally dried to obtain the grafted modified zeolite. In the present embodiment, the zeolite is faujasite.
[0044] As described above, the composite modified high-performance insulating injection molding material for energy storage with flame retardant properties according to the present invention has the following beneficial effects:
[0045] The present invention utilizes the above-mentioned flame-retardant energy storage special composite modified high-performance insulating injection molding material, and has the following advantages compared with the prior art:
[0046] (1) The present invention uses soluble magnesium salt and aluminum salt as raw materials to prepare composite epoxy modified flame retardant phenolic resin, and uses the modified flame retardant phenolic resin to prepare modified high-performance insulating injection molding material, which can further improve the flame retardant effect and longer energy storage cycle; and has less environmental pollution and is environmentally friendly.
[0047] (2) Experiments have found that adding dioctyl phthalate can enhance its toughness.
[0048] In summary, the present invention effectively overcomes various shortcomings of the prior art and has high industrial utilization value.
[0049] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A flame retardant composite modified high-performance insulating injection molding material for energy storage, characterized in that: Composition by weight: 20-35 parts of composite epoxy modified flame retardant phenolic resin; 14-30 parts of filler; 1-5 parts of polyethylene, 1-2 parts of dioctyl phthalate; 10-28 parts of additives; wherein the preparation process steps of the composite epoxy modified flame retardant phenolic resin are: (1) mixing a soluble magnesium salt, a soluble aluminum salt and water to obtain a mixed solution, then dropping the mixed solution into an aqueous solution of sodium dodecylbenzene sulfonate, dropping an aqueous sodium hydride solution to maintain the pH value of the reaction system at 8 to 10, and filtering after the dropwise addition to obtain a modified magnesium-aluminum composite flame retardant; The concentration of the sodium dodecylbenzene sulfonate aqueous solution is 0.01-0.04 mol / L, and the molar ratio of the soluble magnesium salt to the sodium dodecylbenzene sulfonate is 0.2-0.4:1; (2) The modified magnesium-aluminum composite flame retardant is added in an amount of 1 to 5% of the weight of the phenolic resin, and the thermoplastic phenolic resin and the modified magnesium-aluminum composite flame retardant are blended and modified to obtain a composite epoxy modified flame retardant phenolic resin.
2. The flame retardant composite modified high-performance insulating injection molding material for energy storage according to claim 1, characterized in that: The soluble magnesium salt is magnesium nitrate, and the soluble aluminum salt is aluminum nitrate.
3. The flame retardant composite modified high-performance insulating injection molding material for energy storage according to claim 1, characterized in that: The filler is composed of light calcium carbonate and grafted modified zeolite in a weight ratio of 3:1-5.
4. The flame retardant composite modified high-performance insulating injection molding material for energy storage according to claim 3, characterized in that: The grafted modified zeolite is prepared from the following raw materials in weight percentage: 8-16wt% polyimide, 14-20wt% polydimethylsiloxane, and the balance is zeolite; wherein the preparation method of the grafted modified zeolite is: The zeolite is mechanically crushed to 0.5-1 mm, and then the crushed zeolite is washed with hydrochloric acid solution, alcohol and water for 4-6 times respectively and dried, and the treated zeolite is soaked in potassium nitrate solution for 40-60 minutes, the pretreated zeolite is mixed with water with a weight of 2.5-3 times of the pretreated zeolite, and then polydimethylsiloxane is added thereto and ball milled at a speed of 500-600 rpm for 10-15 minutes, and then polyimide is added thereto and ball milled at a speed of 2000-2500 rpm for 120-180 minutes, and finally dried to obtain the grafted modified zeolite.
5. The flame retardant composite modified high-performance insulating injection molding material for energy storage according to claim 4, characterized in that: The zeolite is faujasite.
6. The flame retardant composite modified high-performance insulating injection molding material for energy storage according to any one of claims 1 to 5, characterized in that: The pH value of the reaction system was maintained at 8, 9 or 10.
7. The flame retardant composite modified high-performance insulating injection molding material for energy storage according to any one of claims 1 to 5, characterized in that: The concentration of the sodium dodecylbenzene sulfonate aqueous solution is 0.01 mol / L, and the molar ratio of the soluble magnesium salt to the sodium dodecylbenzene sulfonate is 0.2:1; Or the concentration of the sodium dodecylbenzenesulfonate aqueous solution is 0.02 mol / L, and the molar ratio of the soluble magnesium salt to the sodium dodecylbenzenesulfonate is 0.3:1; Or the concentration of the sodium dodecylbenzenesulfonate aqueous solution is 0.04 mol / L; the molar ratio of the soluble magnesium salt to the sodium dodecylbenzenesulfonate is 0.4:1.
Citation Information
Patent Citations
Preparation method of flame-retardant phenolic resin molding material
CN102875964A
Nano-modified flame-retardant phenolic injection molding material and preparation method thereof
CN104744882A
Heat-resistant flame-retardant soft PVC injection molding material
CN108752799A
Flame-retardant polyethylene composition, flame-retardant polyethylene product and preparation method of flame-retardant polyethylene product
CN117186522A